Activities of daily living independence level for home discharge in stroke patients based on number of caregivers: an analysis of the Japan Rehabilitation Database - SATO, Atsushi (Phys Ther Res, 2017)
Purpose This study aimed to calculate cut-off values of activities of daily living independence level for stroke patient home discharge based on the number of family caregivers. Method The subjects comprised 1442 stroke patients (26 hospitals) who were registered of the Japanese Rehabilitation Database. Receiver operating characteristic curves were used to elucidate the BI and FIM(Ⓡ) instrument scores necessary for home discharge. Analysis was performed for each subject according to the number of family caregivers, i.e., no caregiver, one person, two persons or more, and overall. Result The BI cut-off points that discriminated between home discharge and other were 65/60 points overall, 75/70 points in patients with no caregiver, 65/60 points in patients with one caregiver, and 60/55 points in patients with two or more caregivers. The FIM(Ⓡ) instrument cut-off points were 90/89 points overall, 101/100 points in patients with no caregiver, 87/86 points in patients with one caregiver, and 87/86 points in patients with two or more caregivers. Conclusion Our results indicated that home discharge for patients with many caregivers was possible even with low ADL independence levels, and that there was a large difference in cut-off values depending on the presence or absence of one caregiver.